Rancang Bangun Aplikasi Pencatatan Transaksi Penjualan Tiket Pada PT Gery Anugerah Tour And Travel Di Kupang - Nusa Tenggara Timur - Foe, Fendy Gerry; Nurcahyawati, Vivine; Erstiawan, Martinus Sony (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
PT. Gery Anugerah Tours & Travel is a travel agency company located in the city of Kupang, East Nusa Tenggara. PT. Gery Anugerah Tours & Travel is here to serve the needs of customers for services ticketing domestic and international flights. The management of the company is promoting superior service to customers. In 2013 and 2014 the company experienced a very rapid increase in the sale of airline tickets, with increasing sales then give a positive impact to the company so that the company provides to the customer convenience in transaction using cash or credit. Given the ease of appearing an obstacle in the form of ticket sales related record keeping became sloppy in filing into sales reporting. Ticket sales transaction records that are not neatly arranged this represented a loss of 12% of the records of the sales and the loss of customers who have previously made booking tickets. Any problems that occur, it will be created an information system that will govern the sale of tickets as well as ticket sales reporting company, in order to eliminate the losses incurred earlier. The information system that will be created is the application of transaction records in ticket sales.Keywords: Information System, Sales, ticketing